The Federal Sentencing Guidelines for Organizations: A Framework for Ethical Compliance - Ferrell, O. C. (Journal of business ethics, 1998)
After years of debate over the importance of ethical conduct in organizations, the federal government has decided to institutionalize ethics as a buffer to prevent legal violations in organizations. The key requirements of the Federal Sentencing Guidelines (FSG) are outlined, and suggested actions managers should adopt to improve ethical compliance are presented. An effective compliance program is more a process and commitment than a specific blueprint for conduct. The organization has the responsibility to create an organizational climate to reduce misconduct. The adoption of a FSG compliance program has the potential to substantially lessen organizational penalties if there is due diligence to prevent misconduct. Federal courts determine the effectiveness of an FSG program after a violation occurs.